Reconstruction of Child-Friendly School Through Pancasila Student Profiles Dimensions of Mutual Cooperation - Riana Kristina Suminar; Sabar Narimo; Minsih; Yeny Prastiwi; Laili Etika Rahmawati (Universitas Pendidikan Ganesha, 2023)
The dimension of mutual cooperation is one of the dimensions in the pancasila student profile. This study aims to analyses the child-friendly school reconstruction program through strengthening of the pancasila student profile dimension of mutual cooperation. This is a qualitative research using ethnographic method which was carried out in two public elementary schools. Sources of data in this study are school principals, teachers, and students. Data collection is done by interview, observation, and documentation. Data analysis techniques used interactive analysis techniques consisting of data collection, data reduction, data presentation, and drawing conclusions. The validity of the data test using source triangulation techniques and method triangulation. The results of this study indicate that both elementary schools have implemented the child friendly school reconstruction program in the form of policies, implementation of the learning process, educators and education staff, facilities and infrastructure, participation of children, parents. Reconstruction was carried out by both schools through elements of collaboration, caring and sharing. The conclusion of this study is that the child friendly school program has been reconstructed by the strengthening of the pancasila student profile dimension of mutual cooperation.